Doing justice to history: confronting the past in international criminal courts - Sander, Barrie (Oxford monographs in international humanitarian and criminal law, 2021)
This text examines how historical narratives of mass atrocites are constructed and contested within international criminal courts. In particular, it looks into the important question of what tends to be foregrounded, and what tends to be excluded, in these narratives.